Nonlinear Analysis: Algorithm, Convergence, and Applications 2014 - Song, Yisheng; Chen, Rudong; Li, Guoyin; Yang, Changsen; Yu, Gaohang (Abstract and Applied Analysis, 2014)
The article by H. Wang et al. considered the Cauchy problem for a fifth-order equation and proved its locally well-posed for the initial data in the Sobolev space [figure omitted; refer to PDF] with [figure omitted; refer to PDF] . [...]they also established the ill-posedness for the initial data in [figure omitted; refer to PDF] with [figure omitted; refer to PDF] . The article by C. Li et al. used the principal component analysis method to achieve dimensionality and correlation of input variables and obtained the three major factors affecting membrane fouling most obviously: MLSS, total resistance, and operating pressure, and applied genetic algorithm to optimize the initial weights and the threshold of BP neural network and established the membrane fouling prediction model based on GA-BP network.